QOLP-01. EXPERIENCES FROM PATIENT, CAREGIVER, AND PHYSICIAN SURVEYS ON DIAGNOSIS AND TREATMENT OF BRAIN METASTASES. (12th November 2021) - Kim, Albert; Wang, Gi-Ming; Waite, Kristin; Elder, Scott; Fine, Avery; Ahluwalia, Manmeet; Brat, Daniel; Mehta, Minesh; Page, Robin; Dunbar, Erin; Calderone, Heather; Robins, Debra; et al.
Abstract: The development of brain metastases (BM) is one of the most feared complications of cancer due to the substantial neuro-cognitive morbidity and grim prognosis. In the past decade, targeted therapies and checkpoint inhibitors have demonstrated remarkable intracranial response rates for tumors of multiple histologies. As overall survival for these patients improves, there is a growing need to identify issues surrounding patient survivorship and to standardize physician practice patterns for these patients. To date, there has not been an adequate study to specifically explore these questions of survivorship and practice standardization for patients with advanced cancer and BM. Here, we present results from a cross-sectional survey in which we analyze responses from 237 patients, 209 caregivers, and 239 physicians to identify areas of improvement in the clinical care of BM. In comparing physician and patient/caregiver responses, we found a disparity in the perceived discussion of topics pertaining to important aspects of BM clinical care. We identified variability in practice patterns for this patient population between private practice and academic physicians. Many physicians continue to have patients with BM excluded from clinical trials. Finally, we obtained patient/physician recommendations on high-yield areas for federal funding to improve patient quality of life. Therefore, by identifying potential areas of unmet need, we anticipate this wealth of actionable information will translate into tangible benefits for both patients and caregivers. Future studies are needed to validate our findings.